Faktor-Faktor yang Berhubungan dengan Tingkat Kelelahan Kerja Pada Pengemudi Ojek Online di Wilayah Jakarta Timur Tahun 2019 - Lupita Lupita; Siti Rukayah (Jurnal Persada Husada Indonesia, 2020)
The factor that dominates the occurrence of accidents comes from the human factor, which is 28%, where fatigue experienced by motorcyclists is the main cause of accidents. Online motorcycle taxi drivers who are tired usually don't realize that they are tired, this happens because of an excessive feeling of confidence that they know when they are tired. This study aims to determine the factors related to the level of work fatigue among online motorcycle taxi drivers in the East Jakarta area in 2019. This type of research is a quantitative research with a descriptive survey design using a cross sectional approach. This research was conducted in the East Jakarta area in April 2019. Sampling used the accidental sampling technique. The sample in this study were online motorcycle taxi drivers aged >20 years in the Jatiwaringin area, East Jakarta. the samples taken were 91 people. The research instrument used in this research is to use a questionnaire. Data analysis using univariate and bivariate. The characteristics of the most respondents aged 26-35 years are 29 people, the most respondents' sleep duration is <8 hours, namely 52 people (57.1%), the most respondents' working period is <3 years, namely 63 people (69.2%), the most respondents' working duration is >8 hours, namely 52 people (57.1%), and respondents who experienced high levels of fatigue were 49 people (53.8%). There is a relationship with work fatigue on online motorcycle taxi drivers in the East Jakarta Region, namely length of sleep (p-value = 0.042), duration of work (p-value = 0.024), overtime (p-value = 0.024). Meanwhile, those that are not related to work fatigue are age (p-value = 0.237) and years of service (p-value = 0.053).